Synergic action of L-acetylcarnitine and L-methylfolate in Mouse Models of Stress-Related Disorders and Human iPSC-Derived Dopaminergic Neurons - Orlando, Rosamaria; Ginerete, Roxana Paula; Cavalleri, Laura; Aliperti, Vincenza; Imbriglio, Tiziana; Battaglia, Giuseppe; Zuena, Anna Rita; Nicoletti, Ferdinando; Merlo Pich, Emilio; Collo, Ginetta (Frontiers in Pharmacology, 2022)
The epigenetic agents, L-acetylcarnitine (LAC) and L-methylfolate (MF) are putative candidates as add-on drugs in depression. We evaluated the effect of a combined treatment with LAC and MF in two different paradigms of chronic stress in mice and in human inducible pluripotent stem cells (hiPSCs) differentiated into dopaminergic neurons. Two groups of mice were exposed to chronic unpredictable stress (CUS) for 28 days or chronic restraint stress (CRS) for 21days, and LAC (30 or 100 mg/kg) and/or MF (0.75 or 3 mg/kg) were administered i.p. once a day for 14 days, starting from the last week of stress. In both stress paradigms, LAC and MF acted synergistically in reducing the immobility time in the forced swim test and enhancing BDNF protein levels in the frontal cortex and hippocampus. In addition, LAC and MF acted synergistically in enhancing type-2 metabotropic glutamate receptor (mGlu2) protein levels in the hippocampus of mice exposed to CRS. Interestingly, CRS mice treated with MF showed an up-regulation of NFB p65, which is a substrate for LAC-induced acetylation. We could also demonstrate a synergism between LAC and MF in cultured hiPSCs differentiated into dopamine neurons, by measuring dendrite length and number, and area of the cell soma after 3 days of drug exposure. These findings support the combined use of LAC and MF in the treatment of MDD and other stress-related disorders.